Multi-model inference in comparative phylogeography: an integrative approach based on multiple lines of evidence - Collevatti, Rosane G.; Terribile, Levi C.; Diniz-Filho, José A. F.; Lima-Ribeiro, Matheus S. (Frontiers in Genetics, 2015)
Comparative phylogeography has its roots in classical biogeography and, historically, relies on a pattern-based approach. Here, we present a model-based framework for comparative phylogeography. Our framework was initially developed for statistical phylogeography based on a multi-model inference approach, by coupling ecological niche modelling, coalescent simulation and direct spatio-temporal reconstruction of lineage diffusion using a relaxed random walk model. This multi-model inference framework is particularly useful to investigate the complex dynamics and current patterns in genetic diversity in response to processes operating on multiple taxonomic levels in comparative phylogeography. In addition, because of the lack or incompleteness of fossil record, the understanding of the role of biogeographical events (vicariance and dispersal routes) in most regions worldwide is barely known. Thus, we believe that the expansion of that framework for multiple species under a comparative approach may give clues on genetic legacies in response to Quaternary climate changes and other biogeographical processes.